Using Pregnancy and Parenting Apps and Social Media During COVID-19: Absence and Sociality, Agency and Cultural Negotiations for South Asian–Origin Women in Australia - Sukhmani Khorana; Ruth DeSouza; Bhavya Chitranshi (Social Media + Society)
This article reports on and analyses data from a situated and in-depth project on the experiences of six cisgender South Asian-Australian women/people who gave birth during the COVID-19 pandemic. Prior to the pandemic, negatively racialized women experienced barriers to health care and a lack of social support, which were further exacerbated during the COVID-19 pandemic. International border closures in Australia combined with local mitigation strategies inhibited social and cultural support from families, impacting many migrant mothers/birthing people who gave birth for the first time in Australia. Many hospitals in the states of New South Wales and Victoria instituted restrictions to birthing services as a way of reducing exposure to the coronavirus during the pandemic. Our research suggests that pre-existing limitations of health care providers, digital platforms, and apps with regard to culturally and linguistically diverse (CALD) women in Australia have been amplified during the pandemic. Online Facebook groups from the mothers’ countries of origin or cultural backgrounds, or for mothers who had babies due in the same month, represented a significant source of information and support for the participants. This was particularly important at a time when women’s capacities to engage in traditional cultural practices, which provide practical, emotional, and informational support, were compromised by the inability to garner familial support. We situate these findings in the literature on “performing good motherhood” in neoliberal times and via reliance on digital devices and platforms and what it means for CALD women’s sociality, sense of agency, and negotiations with cultural practices.